Fat mass and obesity-associated (FTO) protein regulates adult neurogenesis. (7th April 2017) - Li, Liping; Zang, Liqun; Zhang, Feiran; Chen, Junchen; Shen, Hui; Shu, Liqi; Liang, Feng; Feng, Chunyue; Chen, Deng; Tao, Huikang; Xu, Tianlei; Li, Ziyi; et al.
Abstract: Fat mass and obesity-associated gene ( FTO ) is a member of the Fe (II)- and oxoglutarate-dependent AlkB dioxygenase family and is linked to both obesity and intellectual disability. The role of FTO in neurodevelopment and neurogenesis, however, remains largely unknown. Here we show that FTO is expressed in adult neural stem cells and neurons and displays dynamic expression during postnatal neurodevelopment. The loss of FTO leads to decreased brain size and body weight. We find that FTO deficiency could reduce the proliferation and neuronal differentiation of adult neural stem cells in vivo, which leads to impaired learning and memory. Given the role of FTO as a demethylase of N6-methyladenosine (m 6 A), we went on to perform genome-wide m 6 A profiling and observed dynamic m 6 A modification during postnatal neurodevelopment. The loss of FTO led to the altered expression of several key components of the brain derived neurotrophic factor pathway that were marked by m 6 A. These results together suggest FTO plays important roles in neurogenesis, as well as in learning and memory.